A method for preparing nickel iron phosphide / nickel molybdate core-shell structure composite electrode material
By growing and processing NiMoO4 precursor in situ on nickel foam, a nickel iron phosphide/nickel molybdate composite electrode material was prepared, which solved the problems of high cost and poor stability of noble metal-based catalysts, and achieved low-cost, high activity and stable electrocatalytic performance.
Patent Information
- Application Number
- CN202210496759.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-04-25
AI Technical Summary
Existing precious metal-based catalysts have high cost, few outputs and poor stability for a long time in electrocatalytic oxygen evolution reactions, making it difficult to meet the needs of large-scale applications.
Ni-iron-iron-molybdate composite electrode material with nanocube array structure is prepared by growing NiMoO4 precursors in situ on nickel foam and by cation exchange and phosphating treatment. This material has a nanocube array structure, is inexpensive and exhibits excellent catalytic properties in OER.
The composite electrode material maintains good stability at a current density of 60mA cm-2, and its electrochemical performance and stability are significantly higher than that of a single phosphide electrode, and the production process is simple and easy to control.
Smart Images

Figure CN115341219B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrolytic electrodes and preparation thereof, and in particular relates to a nickel iron phosphide / nickel molybdate composite electrode material. The invention relates to a preparation method of the composite material. Background Art
[0002] The direct cause of global warming is the greenhouse gases released by human daily activities, and the main reason for the production of greenhouse gases is the use of large amounts of fossil fuels. Economic growth and social industrial development are inseparable from the use of fossil fuels. However, this is followed by the shortage of fossil fuel resources and environmental pollution. Studies have found that electrochemical water splitting is one of the ideal processes for sustainable and environmentally clean energy conversion. As a half-reaction of water decomposition, the slow kinetics of the oxygen evolution reaction leads to excessively high potential, which limits the practical application of electrolytic water decomposition. Therefore, a catalyst is needed to reduce the overpotential and increase the reaction rate, thereby improving the overall efficiency of the electrolytic water reaction.
[0003] The catalysts with the best electrocatalytic oxygen evolution effect are mainly oxides of precious metals Ru and Ir, but their high price and scarce reserves hinder their large-scale application. At the same time, people have also begun to pay attention to the application of transition metals, such as Co, Ni, Fe, Mn, etc., as oxygen production catalysts. In this research direction, people have long recognized that cobalt and nickel-based materials exhibit excellent OER electrocatalytic performance in alkaline media. In recent years, researchers have paid extensive attention to the excellent catalytic performance of transition metal phosphides in electrocatalysis because of their advantages such as low price, abundant storage and high chemical activity.
[0004] Therefore, in view of the defects of traditional precious metal-based catalysts such as high cost, scarce yield, and poor long-term stability, it is necessary to develop an electrocatalyst with low cost, high activity and stability to improve the overpotential of the oxygen evolution reaction.
[0005] This application further studies the nickel foam, uses NiMoO4 as a precursor, and obtains a nickel iron phosphide / nickel molybdate composite electrode material with excellent electrocatalytic oxygen production effect through cation exchange and further phosphating. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a nickel iron phosphide / nickel molybdate composite electrode material. The nickel iron phosphide / nickel molybdate composite electrode material is simple to prepare, the process is easy to control, it is in situ grown on nickel foam, and the production cost is low. The material has a nanocube array structure and exhibits excellent catalytic performance in OER. At 60 mA cm -2 It can maintain good stability even at a current density of 2.5-3.5 W. Compared with other single phosphide electrodes, its electrochemical performance and stability are significantly improved.
[0007] On the other hand, the present invention provides a method for preparing the above-mentioned nickel iron phosphide / nickel molybdate composite material electrode, and the specific steps are as follows: (1) pretreating a nickel foam (NF) substrate to remove oxides and impurities on the surface of the nickel foam substrate; (2) preparing a blue-green solution by nickel nitrate hexahydrate and ammonium molybdate, and immersing the pretreated nickel foam in the blue-green solution to react to obtain yellow NiMoO4 / NF grown on the nickel foam; (3) immersing the above-obtained precursor NiMoO4 / NF in a ferric chloride solution for ion exchange to obtain NiFe PBA / NiMoO4 / NF; (4) phosphating the above-obtained NiFe PBA / NiMoO4 / NF in a tubular furnace to obtain a nickel iron phosphide / nickel molybdate core-shell structure composite electrode material without adding a binder.
[0008] Preferably, in step 1, the pretreatment of the nickel foam substrate comprises the following steps: firstly, the nickel foam NF (1x3cm -2 ) was placed in a hydrochloric acid solution (3 mol / L) and ultrasonicated for about 15 minutes, and then ultrasonicated in anhydrous ethanol and deionized water for 15 minutes respectively, and finally dried for later use.
[0009] Preferably, the step 2 comprises the following steps: first, ammonium molybdate (NH4)6Mo7O 24 ·4H2O and nickel nitrate Ni(NO3)2·6H2O were placed in distilled water to prepare a blue-green solution containing 0.01mol / L ammonium molybdate and 0.04mol / L nickel nitrate, and the pretreated nickel foam was immersed in the blue-green solution. After reacting at 150℃ for 6 hours, the nickel foam was taken out, washed with a large amount of distilled water and ethanol, and dried in a vacuum drying oven. Finally, the yellow precursor NiMoO4 / NF was obtained.
[0010] Preferably, step 3 includes the following steps: dissolving 8.0 mg of potassium ferrocyanide in 100 mL of solution (ethanol: water = 1: 1) to form a light yellow uniform solution, then immersing the above-obtained precursor NiMoO4 / NF in the solution, keeping stirring, and reacting at room temperature for 3 hours. After the reaction, take out the sample and wash it with a large amount of distilled water and anhydrous ethanol, and dry it in a drying oven to obtain NiFe PBA / NiMoO4 / NF.
[0011] Preferably, step 4 includes the following steps: placing a quartz boat containing NiFe PBA / NiMoO4 / NF in a tube furnace, weighing 1.0 g of sodium hypophosphite and placing it at the mouth of the quartz tube, heating (2°C / min) to 350°C under an argon atmosphere, calcining for 2 hours, and cooling naturally to room temperature to obtain a NiFeP / NiMoO4 / NF composite material electrode.
[0012] Compared with the prior art, the present invention has the following beneficial effects: a nickel iron phosphide / nickel molybdate composite electrode material and a preparation method of the electrode are provided, wherein the preparation method is simple and the raw material cost is low, and the prepared nickel iron phosphide / nickel molybdate composite material electrode has significantly improved electrochemical performance and stability compared with a single phosphide electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is a scanning electron microscope image of the precursor NiMoO4 / NF prepared in step 2 of Example 1 of the present invention;
[0014] Figure 2 is a scanning electron microscope image of NiFe PBA / NiMoO4 / NF prepared in step 3 of Example 1 of the present invention;
[0015] Figure 3 is a scanning electron microscope image of NiFeP / NiMoO4 / NF prepared in step 4 of Example 1 of the present invention;
[0016] Figure 4 is the X-ray diffraction spectrum of NiFeP / NiMoO4 / NF prepared in step 4 of Example 1 of the present invention;
[0017] Figure 5 is a transmission electron microscope photograph of NiFeP / NiMoO4 / NF prepared in step 4 of Example 1 of the present invention, wherein (a) and (b) are transmission electron microscope photographs at low and high magnifications, respectively;
[0018] Figure 6 This is a high-resolution transmission electron microscopy image of NiFeP / NiMoO4 / NF prepared in step 4 of Example 1 of the present invention;
[0019] Figure 7 is an element distribution diagram of NiFeP / NiMoO4 / NF prepared in step 4 of Example 1 of the present invention;
[0020] Figure 8 It is a linear scanning curve diagram of OER of the samples prepared in Examples 1, 2, and 3 of the present invention, blank nickel foam, and commercial IrO2 / NF under alkaline conditions;
[0021] Fig. 9 The Tafel curves of the samples prepared in Examples 1, 2, and 3 of the present invention, blank nickel foam, and commercial IrO2 / NF under alkaline conditions;
[0022] Fig.10 This is the stability curve of electrocatalytic oxygen evolution of the sample prepared in Example 1 of the present invention at a high current density of 1.0M KOH; DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] This embodiment is a method for quickly preparing an efficient OER catalyst, which is carried out in the following steps:
[0025] Example 1
[0026] Preparation of catalyst NiFeP / NiMoO4 / NF:
[0027] (1) Pretreatment of nickel foam substrate: The nickel foam was ultrasonically treated in 3 mol / L concentrated hydrochloric acid for 15 minutes, then ultrasonically treated in anhydrous ethanol for 15 minutes, and then ultrasonically treated in distilled water for 15 minutes, and finally dried for later use.
[0028] (2) Preparation of NiMoO4 / NF precursor: First, a certain amount of ammonium molybdate (NH4)6Mo7O 24 ·4H2O and nickel nitrate Ni(NO3)2·6H2O were placed in 50mL of distilled water to prepare a blue-green solution containing 0.01mol / L ammonium molybdate and 0.04mol / L nickel nitrate. The pretreated nickel foam was immersed in the blue-green solution. After reacting at 150℃ for 6 hours, it was taken out and rinsed with a large amount of distilled water and ethanol. After rinsing, it was placed in a vacuum drying oven for drying. Finally, yellow NiMoO4 / NF was obtained.
[0029] (3) Preparation of NiFe PBA / NiMoO4 / NF electrode: 8.0 mg of potassium ferrocyanide was dissolved in 100 mL of solution (ethanol: water = 1:1), and then the precursor NiMoO4 / NF obtained above was immersed in the solution, stirred, and reacted at room temperature for 3 hours. The sample was taken out and washed with a large amount of distilled water and anhydrous ethanol, and dried in a drying oven at 60°C. A NiFe PBA / NiMoO4 / NF electrode was obtained.
[0030] (4) Preparation of NiFeP / NiMoO4 / NF electrode: Take a NiFe PBA / NiMoO4 / NF electrode, place it on a quartz boat, and put it into a quartz tube. Weigh 1.0g of sodium hypophosphite, place it on a quartz boat, put it into the mouth of the quartz tube, heat it to 350℃ (2℃ / min) in an argon atmosphere, calcine it for 2 hours, and take out the sample after the temperature naturally cools to room temperature to obtain a NiFeP / NiMoO4 / NF electrode.
[0031] Example 2
[0032] Preparation of catalyst Ni2P / NiMoO4 / NF:
[0033] (1) Pretreatment of nickel foam substrate: The nickel foam was ultrasonically treated in 3 mol / L concentrated hydrochloric acid for 15 minutes, then ultrasonically treated in anhydrous ethanol for 15 minutes, and then ultrasonically treated in distilled water for 15 minutes, and finally dried.
[0034] (2) Preparation of NiMoO4 / NF precursor: First, a certain amount of ammonium molybdate (NH4)6Mo7O 24 ·4H2O and nickel nitrate Ni(NO3)2·6H2O were placed in 50mL of distilled water to prepare a 0.01mol / L ammonium molybdate solution and a 0.04mol / L nickel nitrate solution to obtain a blue-green solution. The pretreated nickel foam was immersed in the blue-green solution. After reacting at 150℃ for 6 hours, it was taken out and rinsed with a large amount of distilled water and ethanol. After rinsing, it was placed in a vacuum drying oven for drying. Finally, yellow NiMoO4 / NF was obtained.
[0035] (3) Preparation of Ni2P / NiMoO4 / NF electrode: Take a NiMoO4 / NF electrode, place it on a quartz boat, and put it into a quartz tube. Weigh 1.0g of sodium hypophosphite, place it on a quartz boat, put it into the mouth of the quartz tube, heat it to 350℃ under argon atmosphere, calcine for 2 hours, the reaction rate is 2℃ / min, when the temperature is naturally cooled to room temperature, take out the sample, and obtain a black Ni2P / NiMoO4 / NF electrode.
[0036] Example 3
[0037] Preparation of catalyst NiFe PBA / NiMoO4 / NF:
[0038] (1) Pretreatment of nickel foam substrate: The nickel foam was ultrasonically treated in 3 mol / L concentrated hydrochloric acid for 15 minutes, then ultrasonically treated in anhydrous ethanol for 15 minutes, and then ultrasonically treated in distilled water for 15 minutes, and finally dried.
[0039] (2) Preparation of NiMoO4 / NF precursor: First, a certain amount of ammonium molybdate (NH4)6Mo7O 24 ·4H2O and nickel nitrate Ni(NO3)2·6H2O were placed in 50mL of distilled water to prepare a blue-green solution containing 0.01mol / L ammonium molybdate and 0.04mol / L nickel nitrate. The pretreated nickel foam was immersed in the blue-green solution. After reacting at 150℃ for 6 hours, it was taken out and rinsed with a large amount of distilled water and ethanol. After rinsing, it was placed in a vacuum drying oven for drying. Finally, yellow NiMoO4 / NF was obtained.
[0040] (3) Preparation of NiFe PBA / NiMoO4 / NF electrode: 8.0 mg potassium ferrocyanide was dissolved in 100 mL solution (ethanol: water = 1: 1), and then the precursor NiMoO4 / NF obtained above was immersed in the solution, stirred, and reacted at room temperature for 3 hours. After the reaction, the sample was taken out and washed with a large amount of distilled water and anhydrous ethanol, and dried in a drying oven at 60° C. to obtain a NiFe PBA / NiMoO4 / NF electrode.
[0041] Example 4
[0042] Preparation of NiMoO4 / NF precursor:
[0043] (1) Pretreatment of nickel foam substrate: The nickel foam was ultrasonically treated in 3 mol / L concentrated hydrochloric acid for 15 minutes, then ultrasonically treated in anhydrous ethanol for 15 minutes, and then ultrasonically treated in distilled water for 15 minutes, and finally dried.
[0044] (2) Preparation of NiMoO4 / NF precursor: First, a certain amount of ammonium molybdate (NH4)6Mo7O 24 ·4H2O and nickel nitrate Ni(NO3)2·6H2O were placed in 50mL of distilled water to prepare a blue-green solution containing 0.01mol / L ammonium molybdate and 0.04mol / L nickel nitrate. The pretreated nickel foam was immersed in the blue-green solution. After reacting at 150℃ for 6 hours, it was taken out and rinsed with a large amount of distilled water and ethanol. After rinsing, it was placed in a vacuum drying oven for drying. Finally, a yellow NiMoO4 / NF electrode was obtained.
[0045] 2. Electrochemical test:
[0046] Electrochemical tests were performed on the nickel iron phosphide / nickel molybdate composite electrode prepared in the above examples. All electrochemical tests were performed on a CHI760E electrochemical workstation (Shanghai Chenhua). The test parameters were as follows: the prepared nickel iron phosphide / nickel molybdate composite material was the working electrode, the Pt electrode was the counter electrode, the Ag / AgCl electrode was the reference electrode, and the electrolyte was 1.0 M KOH (pH 13.7); before the test, the working electrode retained a working area of 1×1 cm 2 , and the rest were coated with AB glue. All tested potentials were converted to reversible hydrogen electrode RHE and calibrated according to the following formula: E(RHE)=E(SCE)+0.059pH+0.197V. Linear sweep voltammetry (LSV) was measured at a scan rate of 3mV / s, all LSV values were iR compensated, and the electrochemical values of OER were 50% iR. The chronoamperometry (it) voltage was 1.4V vs RHE (without iR compensation).
[0047] The detection and test results are shown in the accompanying drawings and are as follows.
[0048] Figure 1 This is a scanning electron microscope image of the sample prepared in Example 4. It can be seen that the precursor NiMoO4 / NF has a cubic structure, is neatly arranged, and has a relatively smooth surface;
[0049] Figure 2 This is a scanning electron microscope image of the sample prepared in Example 3. It can be seen that the NiFe PBA / NiMoO4 / NF electrode still maintains the nanocube array structure, and the surface of the cube becomes relatively rough.
[0050] Figure 3 This is a scanning electron microscope image of the sample prepared in Example 1. The nickel iron phosphide / nickel molybdate still maintains a good cubic array structure and has a large surface area.
[0051] Figure 4 This is the X-ray diffraction spectrum of NiFeP / NiMoO4 / NF prepared in Example 1, indicating that the composite material was successfully prepared.
[0052] Figure 5 This is a transmission electron microscope image of the NiFeP / NiMoO4 / NF prepared in Example 1. High-magnification TEM can clearly show that it forms a core-shell structure, with NiFeP as its outer shell and NiMoO4 as its inner core.
[0053] Figure 6 This is the high-resolution transmission electron micrograph of NiFeP / NiMoO4 / NF prepared in Example 1. It can be seen that the 110 crystal plane spacing of NiMoO4 is 0.619nm, the 111 crystal plane spacing of Ni2P is 0.22nm, and the 111 crystal plane and 200 crystal plane spacings of Fe2P are 0.28nm and 0.25nm, respectively. It can be seen that NiMoO4, Ni2P, and Fe2P are all present in the prepared sample.
[0054] Figure 7 This is the element distribution diagram of the sample prepared in Example 1. From the diagram, we can see that the five elements Ni, Mo, Fe, P, and O are evenly distributed in the sample, among which P and Fe are mainly distributed in the surface shell. Ni is distributed in the entire cubic column, and Mo is distributed in the core.
[0055] Figure 8 The linear scanning curves of OER of the samples prepared in Examples 1, 2, 3, and 4 of the present invention, blank nickel foam, and commercial IrO2 / NF under alkaline conditions are shown in Figure 1. -2When NiFeP / NiMoO4 / NF is treated with Fe, it has a very small overpotential of 136 mV, which is close to the catalytic performance of commercial IrO2 / NF. This shows that NiFeP / NiMoO4 / NF exhibits excellent OER catalytic performance, and the introduction of Fe can enhance the catalytic performance of Ni2P / NiMoO4 / NF.
[0056] Fig. 9 The Tafel curves of the samples prepared in Examples 1, 2, 3, and 4 of the present invention, blank nickel foam, and commercial IrO2 / NF under alkaline conditions show that NiFeP / NiMoO4 / NF has the smallest Tafel slope of 34.6 mV dec. -1 , which is smaller than that of other catalysts. This shows that the oxygen production kinetic efficiency of the electrocatalyst prepared in Example 1 is better than that of the other catalysts in the comparative example.
[0057] Fig.10 The stability test diagram of the OER of the sample prepared in Example 1 shows that NiFeP / NiMoO4 / NF has good OER stability at a current greater than 50 mA cm -2 It can also maintain activity for a long time at a current density of 2.
Claims
1. A method for preparing a highly active nickel iron phosphide / nickel molybdate core-shell structure composite electrode, characterized in that: Follow the steps below in order: (1) First, place the nickel foam in a hydrochloric acid solution for 15 minutes, and then ultrasonicate it in deionized water and anhydrous ethanol respectively, wash it, and dry it in air for later use; (2) Preparation of precursor NiMoO4 / NF: A certain amount of ammonium molybdate and nickel nitrate hexahydrate were dissolved in 50 mL of distilled water and stirred to obtain a blue-green solution containing 0.01 mol / L of ammonium molybdate and 0.04 mol / L of nickel nitrate. The nickel foam pretreated in step (1) was immersed in the blue-green solution. After reacting at 150° C. for 6 hours, the nickel foam was taken out, washed with distilled water and ethanol, and dried in air. Finally, yellow NiMoO4 / NF was obtained. (3) Synthesis of NiFe PBA / NiMoO4 / NF electrode: Potassium ferrocyanide was dissolved in a 100 mL mixed solution of 50 mL of ethanol and 50 mL of water, and then the precursor NiMoO4 / NF obtained above was immersed in the solution, stirred, and reacted at room temperature for 3 hours. After the reaction was completed, the sample was taken out and washed with a large amount of distilled water and anhydrous ethanol, and dried in a drying oven at 60°C to obtain a NiFe PBA / NiMoO4 / NF electrode; (4) Synthesis of NiFeP / NiMoO4 / NF electrode: Take a NiFe PBA / NiMoO4 / NF electrode, place it on a quartz boat, put it into a quartz tube, weigh 1.0 g of sodium hypophosphite, place it on a quartz boat, put it into the mouth of the quartz tube, heat it to 350°C in an argon atmosphere, and calcine for 2 hours at a heating rate of 2°C / min. When the temperature naturally cools to room temperature, take out the sample to obtain a black nickel iron phosphide / nickel molybdate electrode.
2. The method for preparing a highly active nickel iron phosphide / nickel molybdate composite electrode according to claim 1, characterized in that: The concentration of the hydrochloric acid solution is 3 mol / L.
3. The method for preparing a highly active nickel iron phosphide / nickel molybdate composite electrode according to claim 1, characterized in that: The mass of the ammonium molybdate is 0.0980 g, and the mass of the nickel nitrate hexahydrate is 0.5816 g.
4. The method for preparing a highly active nickel iron phosphide / nickel molybdate composite electrode according to claim 1, characterized in that: The mass of the potassium ferrocyanide is 8.0 mg.
Citation Information
Patent Citations
Efficient total water splitting electrocatalyst IPBAP / Ni2P@MoOx / NF and preparation method thereof
CN110711596A
Preparation and application of bimetallic phosphide growing on foamed nickel and derived by taking Prussian blue analogue as template
CN113275027A
Cited By
Preparation method of nickel-based composite oxygen evolution anode for alkalescent electrolyte
CN120925015A